Wildfires in Northern Portugal: an operational case study in Tabuaço. Issue 3 (1st February 2021) - Rodrigues, André; Ribeiro, Carlos; Reis, Johnny; Sousa, Miguel; Raposo, Jorge
Abstract : The present work is an analysis of the wildfire that occurred in Tabuaço (Portugal). This wildfire developed in a complex topography and under extreme meteorological conditions. The wind was one of the most difficult factors because it increased the rate of spread of the fire front and increased the number of spot fires in front of the head fire. This kind of situation is very often a source of incidents or accidents. Additionally, the fire progressed in zones where the wildland–urban interface was practically non-existent, but also in the areas where the existence of settlements gave rise to critical points, related to the necessity to protect people and property. The suppression manoeuvres of the fire of Tabuaço were carried out in a way that led to a high level of safety, without victims or serious injuries recorded, and so they can be considered an example of a wildfire fighting approach. The use of fire to fight a fire is an important technique when it is well applied. An analysis of the existing conditions, such as geographic characteristics, meteorological situation, topography, fuels and infrastructures of defence against forest fires and fire development and behaviour, are described and analysed in a detailed way.